2008
DOI: 10.1002/cjoc.200890287
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Ovalbumin with Ionic Surfactants

Abstract: The interactions of ovalbumin (OVA) with one anionic surfactant, sodium dodecyl sulfate (SDS), and two cationic surfactants, dodecyl trimethylammonium bromide (DTAB) and cetyl trimethylammonium bromide (CTAB), in water have been studied through fluorescence and UV-Vis spectroscopies and transmission electronic microscopy, combined with the measurement of conductivity. OVA can increase the critical micelle concentrations (cmc) of SDS and CTAB but has little effect on that of DTAB. The interaction between surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…2 shows the UV-Vis absorption spectra of the C1-C4 in CHCl 3 solution. In the UV-Vis absorption spectra, the l max of C1 europium complex in CHCl 3 solution is 325 nm, which is identical to the reported value [17]. While one t-butylphenyl ring was attached to the 4-position of phenyl ring of b-diketone ligand, the l max significantly red shifts to 341 nm for C2 due to the increased conjugation length.…”
Section: Thermal Propertiessupporting
confidence: 74%
“…2 shows the UV-Vis absorption spectra of the C1-C4 in CHCl 3 solution. In the UV-Vis absorption spectra, the l max of C1 europium complex in CHCl 3 solution is 325 nm, which is identical to the reported value [17]. While one t-butylphenyl ring was attached to the 4-position of phenyl ring of b-diketone ligand, the l max significantly red shifts to 341 nm for C2 due to the increased conjugation length.…”
Section: Thermal Propertiessupporting
confidence: 74%
“…[11,12] Ionic surfactants, which are known to show strong associative capacity with proteins in aqueous solutions, present a charged head group attracted to an oppositely charged amino acid residue of a protein and an alkyl chain attracted to nono-polar regions available on the surface and interior of this protein. [13,14] Several methods for studying the interaction between proteins and surfactants, such as Brewster angle microscopy, [12] small angle neutron scattering, [15] light scattering, [16] and quartz crystal microbalance with dissipation (QCM-D), [17][18][19] have been developed. Sjöblom et al [20] studied the adsorption of alkyl trimethyl ammonium bromide with alkyl groups onto solid surfaces and measured the adsorption of these surface-active compounds onto model carbon steel compounds directly by QCM-D.…”
Section: Introductionmentioning
confidence: 99%
“…Following the progress of the reaction via transmission infrared (ATR) spectroscopy, they found that an equimolar concentration of EDC and NHS reagents resulted in high levels of succinimide in the surface layer, and that only a limited “window” of EDC/NHS concentrations would result in sufficient NHS activation (∼5 mM each). In a recent follow-up study, Touahir et al found that the NHS-activation did not go to completion, leaving unreacted carboxylic acid groups able to gain a negative charge at pH > p K a (i.e., for OVA, pH ∼4–6 , ). Furthermore, they identified the optimal temperature range to be ∼4–20 °C, above which NHS-ester levels decreased.…”
Section: Introductionmentioning
confidence: 99%